Determinan Penerapan Anggaran Berbasis Kinerja pada Badan Layanan Umum Rumah Sakit Se-Pulau Sumbawa - Muis, Abdul; M. Furkan, Lalu; Pituringsih, Endar (E-Jurnal Akuntansi; Vol 30 No 10 (2020)DO - 10.24843/EJA.2020.v30.i10.p17, 2020)
This research aims to examine the effect of leadership style, quality of human resources, organizational commitment and internal control systems on the implementation of performance-based budgets. Data obtained by distributing questionnaires to 68 respondents. Data analysis using multiple linear regression analysis. Partially the variables of leadership style, organizational commitment and internal control systems each have a positive and significant effect on the implementation of performance-based budgets, while the quality of human resources has no effect on the implementation of performance-based budgets at BLU Hospitals throughout Sumbawa Island. Keywords: Performance-Based Budget; Leadership Style; Quality Of Human Resources; Organizational Commitment; Internal Control System.